2001
DOI: 10.1074/jbc.m104383200
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II Poisoning by ICRF-193

Abstract: Antineoplastic bis(dioxopiperazine)s, such as meso-2,3-bis(2,6-dioxopiperazin-4-yl)butane (ICRF-193), are widely believed to be only catalytic inhibitors of topoisomerase II. However, topoisomerase inhibitors have little or no antineoplastic activity unless they are topoisomerase poisons, a special subclass of topoisomerasetargeting drugs that stabilize topoisomerase-DNA strand passing intermediates and thus cause the topoisomerase to become a cytotoxic DNA-damaging agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 30 publications
4
68
0
Order By: Relevance
“…However, a more recent study has suggested that ICRF-193 can trap a substantial amount of covalent TOP2␤ (but not TOP2␣)-DNA complexes if Gdn⅐HCl rather than SDS is used to terminate the reaction (28). Their results could explain why ICRF-193 induces preferential degradation of TOP2␤, because only TOP2␤ can be trapped efficiently by ICRF-193 into covalent TOP2␤-DNA complexes.…”
Section: Icrf-193 Does Not Trap Top2-dna Covalent Complexesmentioning
confidence: 95%
“…However, a more recent study has suggested that ICRF-193 can trap a substantial amount of covalent TOP2␤ (but not TOP2␣)-DNA complexes if Gdn⅐HCl rather than SDS is used to terminate the reaction (28). Their results could explain why ICRF-193 induces preferential degradation of TOP2␤, because only TOP2␤ can be trapped efficiently by ICRF-193 into covalent TOP2␤-DNA complexes.…”
Section: Icrf-193 Does Not Trap Top2-dna Covalent Complexesmentioning
confidence: 95%
“…It is also possible that the isoform selectivity of ICRF-193 may contribute to the difference in the involvement of HR. ICRF-193 has recently been shown to target topo II␤ to a greater extent than it targets topo II␣ (46,52). Possibly, the recovery from topo II␤ inhibition may have a stronger preference for NHEJ than topo II␣ inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…First, it specifically inactivates only the ␣ isoform and is certain to remove any structural role. Second, it avoids the complication of side effects, especially DNA DSBs, which were initially thought to be limited to topoII "poisons" such as etoposide, but more recently linked to catalytic inhibitors such as ICRF-193 (van Hille et al, 1999;Huang et al, 2001;Kobayashi et al, 2001;Wang and Eastmond, 2002;. Third, conditional mutagenesis allows complementation studies to be done.…”
Section: Introductionmentioning
confidence: 99%